High-risk human papilloma virus in archival tissues of oral pathosis and normal oral mucosa - Raghu Dhanapal; K Ranganathan; Paturu Kondaiah; R Uma Devi; Elizabeth Joshua; T R Saraswathi (Wolters Kluwer Medknow Publications, 2015)
Objectives: Oral cancer ranks third among all cancers in the Indian population. Human papilloma virus (HPV) plays a significant role in oral carcinogenesis. Population-based subtype variations are present in the HPV prevalence. This study gives an emphasis on the parameters to be considered in formalin fixed paraffin embedded tissues for polymerase chain reaction (PCR)-based research work. Materials and Methods: Cross-sectional study on archival paraffin-embedded tissue samples of oral squamous cell carcinoma (OSCC), epithelial dysplasia, and normal oral mucosa surrounding impacted tooth was amplified by PCR for the E6 gene of HPV type 16 and E1 gene of HPV type 18. Results: HPV 18 was positive in three OSCC cases. There was no statistically significant association of the positivity of HPV with the age, gender or habit. The HPV positive patients had a tobacco habit and were of a younger age group. Conclusion: The presence of HPV in carcinomatous tissue highlights the possible role of HPV in carcinogenesis and archival paraffin embedded tissue specimen can be used for this analysis. Recent studies on genomic analyses have highlighted that the HPV positive tumors are a separate subgroup based on genomic sequencing. The results of a larger retrospective study will help further in our understanding of the role of HPV in carcinogenesis, this study could form the baseline for such follow-up studies.